Online Media Ethics and the Privacy of Politicians in Kosovo - Jahiri, Muhamet; Gërguri, Dren (Information & Media, 2018)
[full article and abstract in English] The pluralism of online media outlets, as well as the objective of these outlets to be the first to inform on events, may possibly lead these outlets to disrespect professional ethics. This paper will discuss the theoretical and ethical aspects of online media, its regulatory framework and particular cases when the respect of ethical standards when reporting on issues of privacy was potentially violated. This paper uses the purposive sampling method and comparative methods. The paper will examine a case study (where the intimate images of a politician were published), and whether ethical standards were respected in that particular case.The article reveals that in the context of information provision for a company, strategic and operational controlling are to be considered the most significant ones. Strategic controlling provides information on how to do the right activity, whereas operational controlling – on how an activity can be done right. The goals of a company can be achieved only through both of them. Tactical controlling is what connects strategic controlling to operational controlling; its paradigm can be expressed through two questions: 1) how to do the right activity right? 2) what should be done when a wrong activity is being done or the activity is being done wrongly? Information provision for the answers to these questions would ensure a direct relation and feedback of strategic and operational controlling. After analyzing the typologization of controlling based on its origin, it was identified that the two main schools of controlling practice exist that led to the development of two different models of controlling: the Anglo-Saxon (American) and European (German). An exemplary controlling model adapted for Lithuanian companies was prepared after comparing the American and German controlling models and evaluating them on the basis of the scope of tasks, dominant orientation, the role of the controller, and the information base. On the basis of this adapted model, an individual information provision controlling system can be created for any Lithuanian company. This article analyzes other types of controlling as well, evaluation of which is important when creating an efficient system for controlling information provision in a particular company.